The genome of the king protea, Protea cynaroides. (10th December 2022) - Chang, Jiyang; Duong, Tuan A.; Schoeman, Cassandra; Ma, Xiao; Roodt, Danielle; Barker, Nigel; Li, Zhen; Van de Peer, Yves; Mizrachi, Eshchar
SUMMARY: The king protea ( Protea cynaroides ), an early‐diverging eudicot, is the most iconic species from the Megadiverse Cape Floristic Region, and the national flower of South Africa. Perhaps best known for its iconic flower head, Protea is a key genus for the South African horticulture industry and cut‐flower market. Ecologically, the genus and the family Proteaceae are important models for radiation and adaptation, particularly to soils with limited phosphorus bio‐availability. Here, we present a high‐quality chromosome‐scale assembly of the P. cynaroides genome as the first representative of the fynbos biome. We reveal an ancestral whole‐genome duplication event that occurred in the Proteaceae around the late Cretaceous that preceded the divergence of all crown groups within the family and its extant diversity in all Southern continents. The relatively stable genome structure of P. cynaroides is invaluable for comparative studies and for unveiling paleopolyploidy in other groups, such as the distantly related sister group Ranunculales. Comparative genomics in sequenced genomes of the Proteales shows loss of key arbuscular mycorrhizal symbiosis genes likely ancestral to the family, and possibly the order. The P. cynaroides genome empowers new research in plant diversification, horticulture and adaptation, particularly to nutrient‐poor soils. Significance Statement: Our chromosome‐level Protea cynaroides genome assembly is the first endemic South African plant genome to be published, and can signify a new wave of research focusing on indigenous fynbos and endemic African plant species. We foresee this serving as increasing visibility of plant genomics research from the African continent and the Global South, and enriching global biodiversity, sustainability, evolution and conservation research.